Cosmopolitanism, Feminism, and Duties to Self. A Kantian Approach - Loriaux, Sylvie (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Feminism has had a sometimes strained relationship with individual freedom: although it has typically been animated by a willingness to liberate women from masculine domination, from the moment it has sought to extend this liberation across cultures or national borders, it has been accused of perpetuating another kind of domination, namely, an imperialist domination. What are we to think of this tension? Is it impossible for a feminist to be a cosmopolitan without being an imperialist? Drawing on the Kantian duty of "rightful honor", this paper argues that the universal value of individual freedom places limits on what women are morally authorised to consent to, and derivately, on the socio-relational environment in which they may legitimately find themselves. Correlatively, it suggests that by insisting on the preservation of one's juridical personality, this duty also allows us to envisage a feminism that is cosmopolitan without being imperialist.